Accident Prevention at Work in Professional Nursing Organization Based on Safety Culture - Suriyawong , Wachira; Tongswas , Tiamsorn (Nursing Journal CMU, 2021)
Many people believed that work-related injury unexpectedly occurred. Registered nurses require 24-hour care for the patient, and as a result of the nature of their work, there is a risk of having to perform procedures that come in contact with bloodborne pathogens, including sharp objects such as syringes. Work-related injury from such services can lead to infection. Consequently, it affects their quality of life, work, emotional state, such as anxiety from exposure to those pathogens. Moreover, there is a higher risk of getting a work-related infection without adherence to the hospital’s safety guidelines. From literature reviews, perceived organizational safety culture positively correlates with decreasing the incidence of work-related injuries. If hospital administrators promote professional nurses’ awareness of organizational safety culture, these incidence rates will decrease. Therefore, this literature review aims to present workplace injury prevention by following the organizational safety culture concept to alleviate workplace injury’s impact among registered nurses and their organization.